Fertility depression among cheese‐making Penicillium roqueforti strains suggests degeneration during domestication. (1st September 2016) - Ropars, Jeanne; Lo, Ying‐Chu; Dumas, Emilie; Snirc, Alodie; Begerow, Dominik; Rollnik, Tanja; Lacoste, Sandrine; Dupont, Joëlle; Giraud, Tatiana; López‐Villavicencio, Manuela
Abstract: Genetic differentiation occurs when gene flow is prevented, due to reproductive barriers or asexuality. Investigating the early barriers to gene flow is important for understanding the process of speciation. Here, we therefore investigated reproductive isolation between different genetic clusters of the fungus Penicillium roqueforti, used for maturing blue cheeses, and also occurring as food spoiler or in silage. We investigated premating and postmating fertility between and within three genetic clusters (two from cheese and one from other substrates), and we observed sexual structures under scanning electron microscopy. All intercluster types of crosses showed some fertility, suggesting that no intersterility has evolved between domesticated and wild populations despite adaptation to different environments and lack of gene flow. However, much lower fertility was found in crosses within the cheese clusters than within the noncheese cluster, suggesting reduced fertility of cheese strains, which may constitute a barrier to gene flow. Such degeneration may be due to bottlenecks during domestication and/or to the exclusive clonal replication of the strains in industry. This study shows that degeneration has occurred rapidly and independently in two lineages of a domesticated species. Altogether, these results inform on the processes and tempo of degeneration and speciation.